The most likely time and place of introduction of BTV8 into Belgian ruminants. - Saegerman, Claude; Mellor, Philip; Uyttenhoef, Aude; Jean-Baptiste Hanon; Kirschvink, Nathalie; Haubruge, Eric; Delcroix, Pierre; Houtain, Jean-Yves; Pourquier, Philippe; Frank Vandenbussche; Verheyden, Bart; Kris De Clercq; et al. (PLoS One, 2010)
BACKGROUND: In northern Europe, bluetongue (BT) caused by the BT virus (BTV), serotype 8, was first notified in August 2006 and numerous ruminant herds were affected in 2007 and 2008. However, the origin and the time and place of the original introduction have not yet been determined. METHODS AND PRINCIPAL FINDINGS: Four retrospective epidemiological surveys have been performed to enable determination of the initial spatiotemporal occurrence of this emerging disease in southern Belgium: investigations of the first recorded outbreaks near to the disease epicenter; a large anonymous, random postal survey of cattle herds and sheep flocks; a random historical milk tank survey of samples tested with an indirect ELISA and a follow-up survey of non-specific health indicators. The original introduction of BTV into the region probably occurred during spring 2006 near to the National Park of Hautes Fagnes and Eifel when Culicoides become active. CONCLUSIONS/SIGNIFICANCE: The determination of the most likely time and place of introduction of BTV8 into a country is of paramount importance to enhance awareness and understanding and, to improve modeling of vector-borne emerging infectious diseases.
Keywords: Animals; Belgium; Bluetongue; Bluetongue virus; Cattle; Cattle Diseases; Ceratopogonidae; Geography; Insect Vectors; Population Density; Retrospective Studies; Reverse Transcriptase Polymerase Chain Reaction; RNA, Viral; Ruminants; Serotyping; Sheep; Sheep Diseases; Time Factors